2016
DOI: 10.18203/2394-6040.ijcmph20162056
|View full text |Cite
|
Sign up to set email alerts
|

Gender preference among reproductive age group women in rural area

Abstract: Background: Skewed sex ratio is an issue of major concern and has long-term social and demographic consequences. In India, the preference for a son is very strong. The preference for a male child and discrimination against the female child are causing the rapid disappearance of female children in India. The main objective was to study the gender preference among rural married women in reproductive age group. Methods: A community based cross sectional study on 220 rural married women of age group 15 to 49 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
3
7
1
Order By: Relevance
“…This might also be a contributing factor to the son preference. Majority of respondents in our study (72.9%) felt that two is the ideal number of children in a family which is in concurrence to the results obtained in studies by Dhande VS et al in Maharashtra 20 and Puri et al in Chandigarh. 21 The Government of India promotes two child norm to reduce the population of the country.…”
Section: Discussionsupporting
confidence: 91%
“…This might also be a contributing factor to the son preference. Majority of respondents in our study (72.9%) felt that two is the ideal number of children in a family which is in concurrence to the results obtained in studies by Dhande VS et al in Maharashtra 20 and Puri et al in Chandigarh. 21 The Government of India promotes two child norm to reduce the population of the country.…”
Section: Discussionsupporting
confidence: 91%
“…In another study high school education was seen in 3.2% of study participants which is less than present study. 11 The present study findings showed that 86% of the study participants were housewives. In another study almost 95% of the study participants were house wives.…”
Section: Discussionsupporting
confidence: 47%
“…The present study findings were similar with other study were about 48% of the study participants were in the age group of 25-30years. 11 High school education was seen in 22.9% of the study participants and 5.7% were post graduates. In another study high school education was seen in 3.2% of study participants which is less than present study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations